Strength Design of Ultra-High-Performance Fiber-Reinforced Cementitious Composites Using Local Ecological Admixture - Rui Ma; Xun Hu; Huiying Hu; Ziyang Tian; Lei Chen; Jinyu Zong (Buildings, 2022)
The ultra-high-performance fiber-reinforced cementitious composite (UHPFRC) is a new generation of building material with extremely high mechanical strength and durability, which can be used for ultra-high, thin-wall or long-span construction, that prolongs the service life of construction in severe environments. In this study, UHPFRC was prepared with a high range of local ecological admixture to decrease the material’s cost and the environmental impact. Raw materials’ proportions, water/binder ratio, fiber-volume contents, and hybrid-fiber ratio were studied on the property improvement of UHPFRC, and an F-test analysis was induced to reveal the important significance on compressive strength. The results demonstrated that the compressive strength of 237.8 MPa was achieved with mineral admixture substitution over 40%. The particle-packing density and the binder reactivity both succeeded on the compressive strength. Water/binder ratio determined the hydration degree and the flowability of UHPFRC, which affected compressive strength through hydration products and microstructure. Also, compressive strength was more sensitive with hybrid-fiber than fiber-volume content. The order of importance for compressive strength was powder proportion > hybrid-fiber ratio > fiber-volume content > water/binder ratio.